Human Resources Management at PT. PLN (Persero) Manokwari Regency - Siagian, Eva Martalina; Sinaga, Nopenas (Universitas Negeri Makassar, 2024)
This study aims to analyze the implementation of human resource management (HR) at PT PLN (Persero) Manokwari Regency. The research method used is qualitative research with a case study approach. Data was collected through in-depth interviews with HR managers, employees, and direct observation of HR activities in the company. The research results show that PT PLN (Persero) Manokwari Regency has implemented various HR management strategies to increase employee productivity and welfare. These strategies include careful recruitment and selection, continuous employee training and development, fair reward systems, and effective internal communications. However, several challenges are still faced, such as an imbalance between labor demand and the availability of highly qualified local employees. This research contributes to the understanding of HR management practices in energy companies and can serve as a guide for other companies in improving their HR performance.